Bacterial profiling of mask waste from terrestrial and marine environment - A. Rakhmawati; B. Octavia; S. Marwati; D. Kristanti (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The utilization of disposable masks during and subsequent to the COVID-19 pandemic has led to the emergence of mask waste. The bacteria that thrive on mask waste have special characteristics. The objective of this research was to identify, choose, and analyze the bacteria present in discarded face masks at landfill sites (Piyungan, Yogyakarta and Jatibarang, Semarang), coastal areas (Tanjung Pasir, Tangerang, and Marina, Semarang), as well as mangrove forests (Teluk Naga, Tangerang, and Tirang, Semarang) situated in Java, Indonesia.METHODS: The bacterial isolation was performed using minimal salt medium. Bacterial isolates were screened in a minimal salt medium supplemented with three types of masks (black duckbill, blue medical, white Korean filter) as the sole carbon and energy source at the various potential of hydrogen levels (5, 7, 9), temperatures (10, 30, 50 degrees Celsius), and sodium chloride concentrations (2.5, 5.0, 7.5 percent). The bacterial strains with the highest optical density values across all treatments were determined through the sequencing of the 16S ribosomal ribonucleic acid gene. These selected bacteria were then evaluated for their ability to produce biofilms under different potential of hydrogen and salt concentrations. The resistance to heavy metals (lead, copper, iron) and antibiotics (penicillin, chloramphenicol, tetracycline, erythromycin, ciprofloxacin, kanamycin) was also investigated.FINDINGS:  A grand total of 183 bacterial strains were obtained, comprising 80 isolates from landfills, 47 isolates from beaches, and 56 isolates from mangroves. The selected bacteria identified as Bacillus cereus, Pseudomonas aeruginosa, Proteus mirabilis, Staphylococcus sciuri, and Staphylococcus arlettae based on 16 svedberg ribosomal ribonucleic acid gene analysis. The chosen strains exhibited the capacity to generate biofilm across various potential of hydrogen and salinity conditions. Furthermore, these strains displayed resilience to heavy metals (such as lead, copper, and iron) as well as resistance to antibiotics (including penicillin, chloramphenicol, tetracycline, erythromycin, ciprofloxacin, and kanamycin).CONCLUSION: Mask waste discovered in landfills, beaches, and mangroves can promote bacterial growth. This study indicated that the selected bacteria are capable of flourishing through the utilization of various mask types as their exclusive carbon and energy source across a wide range of potential of hydrogen levels, temperatures, and salinity concentrations. The ability to produce biofilms, withstand antibiotics, and endure heavy metal ions provides a protective environment for bacteria, enhancing their resilience against environmental stresses, and antimicrobial agents. Analysis of bacterial profiles reveals the intricate connections between microorganisms and their surroundings. The results of this study have implications for public health, environmental pollution, and ecosystem dynamics.